2017
DOI: 10.1016/j.bbi.2016.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Body mass and cognitive decline are indirectly associated via inflammation among aging adults

Abstract: Inflammatory models of neurodegeneration suggest that higher circulating levels of inflammation can lead to cognitive decline. Despite established independent associations between greater body mass, increased inflammation, and cognitive decline, no prior research has explored whether markers of systemic inflammation might mediate the association between body mass and changes in cognitive functioning. To test such a model, we used two longitudinal subsamples (ns = 9066; 12,561) of aging adults from the English … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 45 publications
0
25
1
Order By: Relevance
“…Declining cognitive function has been associated with increased systemic inflammation and inflammatory biomarkers. [14][15][16][17][18]37 Wichmann et al 38 found that those with higher pro-inflammatory IL-6 levels were at a greater risk of cognitive impairment in an elderly cohort where cognitive impairment was classified as an MMSE value of less than 24. Subjects were monitored over a 20 year period and each doubling of IL-6 was associated with a greater risk of cognitive impairment.…”
Section: Alignment To Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Declining cognitive function has been associated with increased systemic inflammation and inflammatory biomarkers. [14][15][16][17][18]37 Wichmann et al 38 found that those with higher pro-inflammatory IL-6 levels were at a greater risk of cognitive impairment in an elderly cohort where cognitive impairment was classified as an MMSE value of less than 24. Subjects were monitored over a 20 year period and each doubling of IL-6 was associated with a greater risk of cognitive impairment.…”
Section: Alignment To Literaturementioning
confidence: 99%
“…13 Aging and indeed cognitive decline has been associated with increased systemic inflammation 14,15 with several studies reporting higher circulating levels of pro-inflammatory cytokines in demented subjects. [16][17][18] Vitamin K has been shown to have anti-inflammatory properties in both in vitro and in vivo studies [19][20][21] and its protective effect in maintaining cognitive integrity is thought to be mediated, in part, through this mechanism. 22 However despite this apparent link, direct studies measuring cognitive function, vitamin K status and inflammation are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic systemic inflammation is increasingly recognised as a contributing factor in the etiology of age-related cognitive decline and neurodegenerative diseases (Bourassa and Sbarra, 2017;Sankowski et al, 2015;Weaver et al, 2002). However, epidemiological studies exploring relationships between markers of inflammation and cognitive function have produced mixed and often inconsistent results (Bettcher and Kramer, 2014;Sharma et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The excess of weight is linked to a poorer quality of life, all-cause mortality, and pathological 21 ageing (Bischof and Park, 2015;Vallis, 2016). Cognitive alterations could be mediated by adiposity-22 induced low-grade chronic inflammatory states (Bourassa and Sbarra, 2017;Lasselin et al, 2016;23 Spyridaki et al, 2016). A growing body of research stresses the fact that the organism adapts to 24 energy surplus situations via immune and neuroendocrine adaptations that, in turn, can negatively 25 impact the brain in the long-run (Guillemot-Legris and Muccioli, 2017; Reilly and Saltiel, 2017).…”
Section: Introduction 18mentioning
confidence: 99%